Information, intermediaries, and international migration - Samuel Bazzi; Lisa Cameron; Simone Schaner; Firman Witoelar (W.E. Upjohn Institute for Employment Research, 2022)
Job seekers face substantial information frictions, especially in international labor markets where intermediaries match prospective migrants with overseas employers. We conducted a randomized trial in Indonesia to explore how information about intermediary quality shapes migration outcomes. Holding access to information about the return to choosing a high-quality intermediary constant, intermediaryspecific quality disclosure reduces the migration rate, cutting use of low-quality providers. Workers who do migrate receive better pre-departure preparation and have improved experiences abroad, despite no change in occupation or destination. These results are not driven by changes in beliefs about average provider quality or the return to migration. Nor does selection explain improved outcomes for those who migrate with quality disclosure. Together, our findings are consistent with an increase in the option value of search: with better ability to differentiate offer quality, workers search longer, select higher-quality intermediaries, and ultimately have better migration experiences.
Keywords: F22; O15; D83; L15; 330; International migration; information; middlemen; quality disclosure; search